PERAN LINTAS BUDAYA TERHADAP PENDAMPINGAN KONSELING DI ASRAMA PUTRI SEKOLAH TINGGI TEOLOGI EKUMENE JAKARTA (POIMEN Jurnal Pastoral Konseling, 2024)
Every individual has a different way of thinking. This way of thinking covers all life that is influenced by the environment, one of which is culture. In carrying out counseling assistance, it is necessary for counselors or companions to do cross-cultural work to understand different ways of thinking for STT Ekumene Jakarta students, especially those who live in the Girls Dormitory. Because without understanding the way of thinking of each individual will trigger a conflict in the continuity of counseling assistance. This research was conducted to find out how big the role of cross-culturalism is in the success of counseling assistance at the STT Ekumene Girls Dormitory and what counseling techniques are used in cases like this.